Concerto à Brasileira - Wolff, Daniel (Manaus Novo disc, 2000)
Brazilian guitarist and composer Daniel Wolff, aided by conductor Tiago Flores directing the Orquestra de Câmara da ULBRA, directed this Brazilian program. Given that this is Wolff's debut recording as a leader, both as orchestrator and soloist, the stakes are quite high. Wolff chose the works of such notable composers as Thiago de Mello, Ernesto Nazareth, and Radamés Gnattali for this outing. Nazareth was the most obvious choice in that Wolff was commissioned by conductor Ferdi Gerling to create a concerto from Nazareth's solo piano pieces for that instrument and orchestra. Titled The Three Faces of Ernesto, Wolff chose The Third Face of Ernesto for performance here. Utilizing three famous themes by the composer, and one inspired by Emerson, Lake & Palmer's song "The Sheriff," Wolff scored the piece for two guitarists and strings. With wonderfully diverse moods and variations, Wolff has given listeners a work of both drama and whimsy. There are two pieces by de Mello here, and his Amadeste is the one that is most profound. Influenced by the desert train inside Brazil, the shadows and light cast by the orchestra over the fluid and knotty guitar work contrast the beauty and harshness of the terrain. Reflections (A Hug for Ayla) is sweeter and more romantic in scope, yet also creates some tension in terms of longing -- the strings come to the fore as instruments of both joy and tears. Wolff's Concerto para Clarinete e Orquestra de Cordas is a three-movement work with humor, depth, and sweeping legato passages for the soloist. In all, a gorgeously expressionistic recording that offers listeners the rainbow of Brazilian classical achievements in the 20th century.